A Study of the Formation Morphology and Phase Equilibrium of Fractured Methane Hydrates. Issue 5 (October 2015) - Sun, Youhong; Zhang, Guobiao; Guo, Wei; Li, Bing; Li, Shengli; Su, Kai; Jia, Rui
Natural gas hydrates mostly fill in the pores or fractures of host sediments and fractured gas hydrates are the main reservoir type in the Qilian mountain region of China. The process of gas production from hydrates can be influenced by the pore structures, fracture properties and mineral compositions of the host sediments. To determine whether the formation and phase equilibrium of hydrates are affected by the properties of the fractures, including the angle and width, formation experiments on methane hydrates were conducted using fracture media composed of artificial sandstone and natural mudstone. The phase equilibrium points for the methane hydrates hosted in fracture mudstone were measured using multi-stage heating. The experimental results indicate that the gas hydrates hosted within the fracture media grew faster. However, there were obvious differences in the methane hydrate formation morphologies for the two types of fracture media: the main occurrences of gas hydrates in sandstone were massive formations, and layered gas hydrates were formed along the fracture surfaces in mudstone. Additionally, a comparison of the phase equilibrium between the fractured CH4 and bulk phase CH4 hydrates indicated that the fracture scale did not have a significant influence on the thermodynamic equilibrium of the CH4 hydrates for the experimental conditions and also implied that fracture properties had an insignificant impact on the hydrate stability zone.